State Sovereignty in the Sahadow of Great Power - Khadka, Prakriti (KDCBAR Law Journal, 2025)
The research explores the relationship between foreign policy autonomy, sovereignty, and great power politics, using Nepal as a case study. It reveals that Nepal faces challenges like economic dependencies, domestic political fragmentation, and rivalry between India and China. Despite these, it has managed through strategies like non-alignment, diplomatic diversification, strategic hedging, and active multilateral engagement. The study recommends further economic diversification and agile diplomacy for resilience. The research concludes that maintaining sovereignty requires a continuous and pragmatic balancing act, and it recommends further economic diversification, strengthened domestic institutions, and agile diplomacy to enhance resilience and safeguard national interests in an increasingly contested regional order.